‘This is neither Swedish nor Western and doesn’t belong here’ - Johanna Sixtensson; Paula Mulinari; Carina Listerborn (Journal of Digital Social Research)
This article analyses written online responses to Swedish retail stores’ social media advertisements broadly addressing the Muslim celebration of Ramadan. It is based on a selection of 19 social media advertisement posts that together generated a total of 2988 responses in discussion threads. The customer responsive comments are analysed through the theoretical lens of race and racism in the digital society and theories of everyday nationhood and nationalism. At large, the result shows that the social media platforms can be seen as facilitators of anti-Muslim racism. However, the advertisements and the responses to them, which express dislike of as well as support for the retailers, Muslim traditions and the Muslim community, illustrate a negotiation of nationhood which is characterized on the one side by racist anger and fear of loss of nation, and on the other side by support for inclusion. Inspired by the concept of ‘predatory inclusion’, the article argues that this paradoxical phenomenon illustrates both inclusion and exclusion. The retail stores’ social media platforms are not only spaces of hatred against Muslims but also a space in which resistance to anti-Muslim racism is articulated and where constructions of Swedishness are challenged.